Composite particles and method for producing same
Patent Information
- Application Number
- JP2021025905
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-02-22
- Publication Date
- 2025-03-05
- Estimated Expiration
- 2041-02-22
AI Technical Summary
【0013】 本発明によれば、有機溶媒および水溶媒の両者と親和性が高く且つ誘電率が高い複合粒子が得られる。
Smart Images

Figure 0007639389000003 
Figure 0007639389000004 
Figure 0007639389000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a composite particle and a method for producing the same. [Background technology]
[0002] Various circuit boards are used in electronic devices. The higher the dielectric constant of the board material, the smaller the signal propagation wavelength. Therefore, to miniaturize circuit boards used in antennas and power amplifiers, it is desirable to use board materials with high dielectric constants. In addition, since the higher the frequency, the greater the signal transmission loss, it is desirable for the board material to have a low dielectric tangent. Therefore, it is preferable for the board material to contain a high content of alkaline earth metal titanate particles (such as barium titanate or strontium titanate) as an inorganic filler.
[0003] A method has been proposed for increasing the affinity of alkaline earth metal titanate particles for solvents and resins by treating the surfaces of the particles, which can increase the content of inorganic fillers in the substrate material.
[0004] Patent Document 1 (JP 2010-24094 A) discloses "a modified perovskite-type complex oxide in which the particle surface of a perovskite-type complex oxide is primarily coated with a coating layer containing at least Al2O3 and is secondarily coated with at least one selected from the group consisting of SiO2, TiO2, ZrO2 and Nd2O3, wherein the primary coating is formed by firing a hydrolysis product of a hydrolyzable Al2O3 precursor, and the secondary coating is formed by firing at least one hydrolysis product selected from the group consisting of a hydrolyzable SiO2 precursor, a hydrolyzable TiO2 precursor, a hydrolyzable ZrO2 precursor and a hydrolyzable Nd2O3 precursor."
[0005] Patent Document 2 (WO 2016 / 140305) discloses a barium titanate particle powder characterized in that "the average particle size of the primary particles is 10 nm or more and 60 nm or less, the particle coefficient of variation (the value obtained by dividing the standard deviation of the particle size distribution by the average particle size) is 0.35 or less, and the amount of Ba ions eluted from the powder into an aqueous solvent is 1000 ppm or less."
[0006] Patent Document 3 (JP 2003-342077 A) discloses a method for producing a dielectric ceramic raw powder, comprising: a first step of dispersing a perovskite (ABO3) ceramic raw powder in an aqueous medium to obtain a slurry; a second step of adding one or more compounds selected from a group of compounds containing minor component elements to the slurry obtained after the first step; and a third step of spray-drying the slurry obtained after the second step to obtain a dielectric ceramic raw powder, the method being characterized in that the spray-drying in the third step is a method of spraying the slurry obtained after the second step into a heat-resistant porous bag-shaped or cylindrical drying chamber, and separating the slurry into a dried exhaust gas and a dielectric ceramic raw powder by hot air supplied into the drying chamber. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2010-24094 A [Patent Document 2] International Publication No. 2016 / 140305 [Patent Document 3] JP 2003-342077 A Summary of the Invention [Problem to be solved by the invention]
[0008] However, it is difficult to obtain particles with sufficiently high affinity for solvents and resins by conventional surface treatments.Furthermore, there is a drawback in that the dielectric constant decreases as the proportion of the compound attached to the surface of the above-mentioned particles increases.
[0009] On the other hand, the use of organic solvents is expensive to manufacture and has a high environmental impact, so there is a demand to reduce the use of organic solvents. If aqueous solvents could be used, it would be advantageous in terms of manufacturing costs and the environment. Therefore, there is a demand for particles that have high affinity with both organic solvents and aqueous solvents.
[0010] In this situation, one object of the present invention is to provide composite particles having high affinity with both organic solvents and aqueous solvents and a high dielectric constant, and a method for producing the same. [Means for solving the problem]
[0011] One aspect of the present invention relates to a method for producing composite particles, which comprises composite oxide particles having a composition represented by the formula ATiO3 (wherein A represents at least one element selected from the group consisting of Ba, Sr, and Ca) and a layer of an aluminum compound disposed on the surface of the composite oxide particles, and includes the steps of: (i) preparing a slurry containing the composite oxide particles by dispersing the composite oxide particles in an aqueous liquid; (ii) adding an aluminum-containing water-soluble compound and an acid to the slurry; and (iii) drying the particles obtained by the step (ii), in which the step (ii) is carried out while maintaining the pH of the slurry in the range of 8.0 to 10.0 and the temperature of the slurry in the range of 50 to 90°C; and in the step (ii), the ratio of the mass Wa of the water-soluble compound added to the slurry in terms of aluminum oxide to the mass Wp of the composite oxide particles in the slurry is defined as X1 (mass %), and the specific surface area of the composite oxide particles is defined as Z (m 2 / g), the X1 (mass%) and the Z (m 2 / g) satisfies 1 / 30≦X1 / Z≦1 / 3.
[0012] Another aspect of the present invention relates to a composite particle, which comprises a composite oxide particle having a composition represented by the formula ATiO3 (wherein A represents at least one element selected from the group consisting of Ba, Sr and Ca) and an aluminum compound layer disposed on the surface of the composite oxide particle, in which the average value of the ratio La / Lp of the perimeter Lp (μm) of the surface of the composite oxide particle in a cross section of the composite particle photographed by a transmission electron microscope to the perimeter La (μm) of the portion of the surface covered with the layer in the cross section is 0.30 or more, and the average thickness of the layer is in the range of 1.5 nm to 4.5 nm. Effect of the Invention
[0013] According to the present invention, composite particles having high affinity with both organic solvents and aqueous solvents and a high dielectric constant can be obtained. [Brief description of the drawings]
[0014] [Figure 1] FIG. 1 is a transmission electron microscope photograph of an example of particle A2 (invention example) produced in the Examples. [Diagram 2] FIG. 2 is a transmission electron microscope photograph of another example of particle A3 (invention example) produced in the Examples. [Diagram 3] FIG. 3 is a transmission electron microscope photograph of another example of particles CA6 (comparative example) produced in the Examples. [Figure 4] FIG. 4 is a transmission electron microscope photograph of another example of particles CA7 (comparative example) produced in the Examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] In the following, the embodiment of the present invention will be described with examples, but the present invention is not limited to the examples described below. In the following description, specific numerical values and materials may be exemplified, but other numerical values and materials may be applied as long as the effects of the present invention can be obtained. In this specification, when "numerical value A to numerical value B" is mentioned, the range includes numerical value A and numerical value B. In this specification, "particles" can be read as "powder".
[0016] (Method of manufacturing composite particles) The manufacturing method of this embodiment is a manufacturing method of composite particles including composite oxide particles having a composition represented by the formula ATiO3 (wherein A represents at least one element selected from the group consisting of Ba, Sr, and Ca) and a layer of an aluminum compound disposed on the surface of the composite oxide particles. The composite oxide particles and composite particles may be referred to as "particles (T)" and "composite particles (P)" below, respectively. The layer of the aluminum compound may be referred to as "layer (L)". The manufacturing method of this embodiment may be referred to as "manufacturing method (M)" below. In this specification, in descriptions other than those that are directed to only one particle, the particle may be read as a powder (a powder composed of a large number of particles).
[0017] The particles (T) have a perovskite crystal structure, and preferably have a single-phase perovskite crystal structure. The particles (T) may contain unavoidable impurities, and the content of the unavoidable impurities is, for example, 1 mass % or less.
[0018] The production method (M) includes steps (i), (ii), and (iii) in this order, which are described below.
[0019] (Step (i)) Step (i) is a step of preparing a slurry containing composite oxide particles (particles (T)) by dispersing the particles (T) in an aqueous liquid. The composition of the particles (T) is represented by the formula ATiO3 (wherein A represents at least one element selected from the group consisting of Ba, Sr, and Ca). Examples of the particles (T) include barium titanate particles (BaTiO3), strontium titanate particles (SrTiO3), and calcium titanate particles (CaTiO3). The element A in the formula ATiO3 may be one element, two elements, or three elements. The element A may include at least Ba.
[0020] The particles (T) may be commercially available particles, or may be synthesized by a known method. The specific surface area Z (m 2 / g) is 2.0 to 80m 2 / g range (e.g. 4.0~15m 2 / g). The specific surface area Z(m 2 / g) from 4.0 to 15m 2 / g range (e.g. 4.0~14m 2 / g), particles having a large dielectric constant and less susceptible to aggregation can be obtained.
[0021] The average particle size of the particles (T) may be in the range of 10 nm to 500 nm (for example, in the range of 70 nm to 350 nm). By setting the average particle size in the range of 70 nm to 350 nm, particles having a large dielectric constant and less susceptible to aggregation can be obtained. Here, the average particle size of the particles (T) can be calculated from the specific surface area. First, the specific surface area of the particles (T) is measured. Then, assuming that the particles (T) are spherical particles, the average particle size is calculated using the density and specific surface area of the particles (T). A known density based on the composition of the particles may be applied to the density of the particles (T).
[0022] The aqueous liquid is a liquid in which the proportion of water in the liquid components is 50% by mass or more. The proportion of water in the liquid components of the aqueous liquid may be 60% by mass or more, 80% by mass or more, 90% by mass or more, or may be 100%. The liquid components of the aqueous liquid may contain an organic solvent other than water. However, from the viewpoint of reducing production costs and environmental load, the proportion of water in the liquid components of the aqueous liquid is preferably high, and is preferably 90% by mass or more (95% by mass or more or 100% by mass). A preferred example of the aqueous liquid is water that does not contain an organic solvent. The water used in the aqueous liquid may be ion-exchanged water (deionized water). Examples of organic solvents contained in the aqueous liquid include alcohol.
[0023] The aqueous liquid may be an aqueous solution, or may contain additives other than the particles (T). For example, an additive such as a dispersant may be dissolved in the aqueous liquid. There is no particular limitation on the dispersant, and a known dispersant may be used. Examples of dispersants include ammonium polyacrylate.
[0024] The content of particles (T) in the slurry prepared in step (i) is not particularly limited. The content may be in the range of 3 to 70 mass% (for example, in the range of 5 to 60 mass%). The slurry may be prepared, for example, by adding particles (T) to an aqueous liquid and stirring the mixture. There is no particular limit to the stirring method, and any known stirring method may be used.
[0025] When the pH of the slurry obtained by dispersing the particles (T) in the aqueous liquid is not within the range controlled in step (ii) (e.g., 8.0 to 10.0), step (i) may include a step of adjusting the pH of the slurry to the range controlled in step (ii) (e.g., 8.0 to 10.0). For example, the pH can be adjusted by adding an acid or an alkali to the slurry. From another perspective, step (i) is a step of preparing a slurry in which the composite oxide particles are dispersed in the aqueous liquid and the pH is within a predetermined range. The predetermined range is the range controlled in step (ii) (e.g., 8.0 to 10.0).
[0026] (Step (ii)) Step (ii) is a step of adding an aluminum-containing water-soluble compound and an acid to the above-mentioned slurry. Step (ii) is carried out while maintaining the pH of the slurry in the range of 8.0 to 10.0 and the temperature of the slurry in the range of 50 to 90°C. In step (ii), the ratio of the mass Wa of the water-soluble compound added to the slurry in terms of aluminum oxide to the mass Wp of the composite oxide particles (particles (T)) in the slurry is defined as X1 (mass%), and the specific surface area of the composite oxide particles is defined as Z (m 2 / g), X1 (mass%) and Z (m 2 / g) satisfies 1 / 30≦X1 / Z≦1 / 3.
[0027] The mass of the water-soluble compound containing aluminum, calculated as aluminum oxide, means the mass of aluminum oxide containing the same number of aluminum atoms as the number of aluminum atoms contained in the water-soluble compound containing aluminum. X1 is calculated by the formula: X1 (mass%) = 100 × Wa / Wp.
[0028] By the step (ii), a layer (L) of an aluminum compound is disposed on the surface of the particle (T). As shown in the examples described later, by the step (ii), a composite particle (P) having high affinity with both an organic solvent and an aqueous solvent and a high dielectric constant can be obtained. The aluminum compound constituting the layer (L) can vary depending on the type of aqueous compound added to the slurry, and examples thereof include aluminum hydroxide, aluminum oxide, and the like. The aluminum compound constituting the layer (L) may be one type of aluminum compound, or may contain two or more types of aluminum compounds.
[0029] In step (ii), the pH of the slurry is 8.0 or more, and may be 8.1 or more. The pH is 10.0 or less, and may be 9.8 or less. For example, the pH may be maintained in the range of 8.1 to 9.8.
[0030] Step (ii) is usually carried out while stirring the slurry. That is, step (ii) is usually a step of adding an aluminum-containing water-soluble compound and an acid to the above-mentioned slurry and mixing them. There is no limitation on the method of stirring the slurry, and a known stirring method may be used.
[0031] In step (ii), the pH of the slurry fluctuates preferably within 1.0, more preferably within 0.4. For example, in step (ii), the pH of the slurry may be within ±0.5 of a predetermined value in the range of 8.5 to 9.5. Alternatively, in step (ii), the pH of the slurry may be within ±0.2 of a predetermined value in the range of 8.2 to 9.8. By keeping the pH fluctuation in step (ii) within 1.0, it is possible to make the thickness of the aluminum compound layer formed more uniform.
[0032] In a preferred example, in step (ii), the water-soluble compound is added to the slurry while maintaining the pH of the slurry in the range of 8.0 to 10.0 by adding an acid to the slurry. For example, the pH of the slurry may be maintained in a predetermined range by adjusting the amount of acid added while monitoring the pH of the slurry. This example of step (ii) usually includes a time during which the acid and the water-soluble compound are added simultaneously. The acid may be added to the slurry continuously or intermittently.
[0033] In step (ii), the temperature of the slurry is maintained in the range of 50 to 90° C. It is believed that by maintaining the temperature of the slurry in the range of 50 to 90° C., the layer (L) of the aluminum compound formed can be made dense. Therefore, it is believed that maintaining the temperature of the slurry in the range of 50 to 90° C. enhances the affinity of the composite particles for both the organic solvent and the aqueous solvent.
[0034] In step (ii), the temperature of the slurry is preferably maintained in the range of 70 to 90° C. By keeping the temperature of the slurry in the range of 70 to 90° C., the layer (L) can be made denser, and the affinity of the composite particles for both the organic solvent and the aqueous solvent can be further increased.
[0035] Examples of the water-soluble compound (water-soluble compound containing aluminum) added to the slurry include sodium aluminate (NaAlO2), potassium aluminate (KAlO2), basic polyaluminum hydroxide, etc. The water-soluble compound may be added to the slurry in a state dissolved in a liquid (for example, in the state of an aqueous solution).
[0036] The water-soluble compound may be a compound whose aqueous solution is alkaline. Examples of such water-soluble compounds include sodium aluminate, potassium aluminate, and the like.
[0037] In addition, from another point of view, the water-soluble compound containing aluminum is a water-soluble aluminum compound. This aluminum compound is different from the aluminum compound constituting the layer (L). Therefore, the aluminum compound constituting the layer (L) can be read as the first aluminum compound, and the water-soluble compound added to the slurry can be read as the second aluminum compound.
[0038] Examples of acids added to the slurry include nitric acid (aqueous nitric acid), hydrochloric acid, sulfuric acid, oxalic acid, acetic acid, phosphoric acid, lactic acid, citric acid, formic acid, boric acid, malic acid, tartaric acid, maleic acid, etc. The amount of acid added to the slurry is adjusted according to the pH of the slurry. In one preferred example, the water-soluble compound is sodium aluminate and the acid is nitric acid.
[0039] X1 (mass%) and Z (m 2 / g) satisfies 1 / 30≦X1 / Z≦1 / 3. In other words, X1 (mass%) and Z (m 2 / g) satisfies 0.033≦X1 / Z≦0.333. The value of X1 / Z is 0.033 or more, and may be 0.050 or more, or 0.073 or more. The value of X1 / Z may be 0.333 or less, and may be 0.219 or less. These lower and upper limits can be combined arbitrarily. For example, the value of X1 / Z may be in the range of 0.033 to 0.333, the range of 0.033 to 0.219, or the range of 0.073 to 0.219.
[0040] (Step (iii)) Step (iii) is a step of drying the particles obtained by step (ii). Step (iii) may include a step of drying the slurry that has been subjected to step (ii). In this case, the slurry may be washed and then dried. For example, the slurry may be placed on a funnel equipped with filter paper and washed, and the remaining solid matter (cake) may be filtered and dried. There is no particular limitation on the drying conditions, and drying may be performed by heating and / or reducing pressure. The drying temperature may be in the range of 100°C to 150°C (for example, in the range of 110 to 140°C). However, if the drying temperature is too high, the physical properties of the particles may change. The drying time may be in the range of 1 to 100 hours (for example, in the range of 10 to 80 hours).
[0041] The particles obtained in step (ii) may or may not be changed by the treatment in step (iii) (e.g., heat treatment during drying). Composite particles (P) are produced by a production method including steps (i) to (iii).
[0042] A layer (L) is present on at least a part of the surface of the composite particle (P). The layer (L) is formed on the surface of the particle (T) so as to contact the particle (T). In the manufacturing method of this embodiment, a step of forming another layer on the layer (L) is not usually performed. That is, the layer formed on the particle (T) is usually only the layer (L). The effect of the present invention is obtained by exposing the layer (L) on the surface. However, another layer may be formed on a part of the surface of the layer (L) to the extent that the effect of the layer (L) is obtained. In addition, the composite particle (P) may be subjected to a surface treatment to the extent that the effect of the layer (L) is obtained. Examples of the surface treatment include treatment with a silane coupling agent. By performing a surface treatment with a silane coupling agent, the affinity to an organic solvent can be increased. There is no particular limitation on the silane coupling agent and the treatment method using it, and a known silane coupling agent and treatment method used for surface treatment of particles may be applied.
[0043] In one aspect, the present invention provides composite particles having a high dielectric constant and an affinity for an organic solvent and an affinity for an aqueous solvent controlled at a desired balance, and a method for producing the same. For example, by subjecting the composite particles (P) to a surface treatment, it is possible to easily change the balance between the affinity for an organic solvent and the affinity for an aqueous solvent. As described above, the production method of the present invention can achieve high affinity for both organic solvents and aqueous solvents.
[0044] (composite particles) The composite particle of this embodiment is a composite particle (composite particle (P)) including a composite oxide particle (particle (T)) having a composition represented by the formula ATiO3 (wherein A represents at least one element selected from the group consisting of Ba, Sr, and Ca) and an aluminum compound layer (layer (L)) arranged on the surface of the composite oxide particle. The average value of the ratio La / Lp between the perimeter Lp (μm) of the surface of the particle (T) in a cross section of the composite particle (P) photographed with a transmission electron microscope and the perimeter La (μm) of the portion of the surface covered with the layer (L) in the cross section is 0.30 or more. The average thickness of the layer (L) is in the range of 1.5 nm to 4.5 nm. The composite particle of this embodiment has high affinity with both organic solvents and aqueous solvents and has a high dielectric constant. Hereinafter, the average value of the ratio La / Lp may be referred to as the "average value Ave (La / Lp)" or "coverage ratio".
[0045] The composite particles of this embodiment can be manufactured by the manufacturing method (M) of this embodiment. Therefore, the matters explained in the manufacturing method (M) can be applied to the composite particles of this embodiment. Furthermore, the matters explained about the composite particles of this embodiment may be applied to the manufacturing method (M). An example of the composite particles of this embodiment is the composite particles (P) manufactured by the manufacturing method (M). However, the composite particles of this embodiment may be manufactured by a manufacturing method other than the manufacturing method (M).
[0046] The average value Ave(La / Lp) is 0.30 or more, and may be 0.31 or more, or 0.33 or more. There is no particular limitation on the upper limit of the average value Ave(La / Lp), and it may be 1.0 or less, 0.80 or less, 0.70 or less, or 0.60 or less. These lower and upper limits can be combined arbitrarily. For example, the average value Ave(La / Lp) may be in the range of 0.30 to 1.0, 0.30 to 0.70, or 0.30 to 0.60, and the lower limit of these ranges may be 0.31. When the entire surface of the particle (T) is covered with the layer (L), the average value Ave(La / Lp)=1.
[0047] The average value Ave(La / Lp) can be obtained by the following method. First, the perimeter of the surface of a composite oxide particle in a cross section of one composite particle photographed with a transmission electron microscope is taken as Lp (μm), and the perimeter of the portion of the surface covered with layer (L) in the cross section is taken as La (μm), and the ratio La / Lp is obtained. Then, a predetermined number (e.g., 10) of composite particles are arbitrarily selected, the ratio La / Lp is obtained for each particle, and the arithmetic average is calculated to obtain the average value Ave(La / Lp).
[0048] The average thickness of the layer (L) is 1.5 nm or more, and may be 1.7 nm or more, or 2.2 nm or more. The average thickness of the layer (L) is 4.5 nm or less, and may be 4.0 nm or less, or 3.3 nm or less. These lower and upper limits can be combined arbitrarily. For example, the average thickness of the layer (L) may be in the range of 1.7 nm to 4.0 nm. The average thickness of the layer (L) is determined by a method described in the examples.
[0049] The ratio of the mass Wa of the water-soluble compound added to the slurry in terms of aluminum oxide to the mass Wp of the composite oxide particles (particles (T)) in the slurry in the above step (ii) is defined as X1 (mass%). Also, the ratio of the mass WA of the aluminum compound constituting the layer (L) in terms of aluminum oxide to the mass WP of the composite oxide particles (particles (T)) in the composite particle (P) is defined as X2 (mass%). The relationship between X2 (mass%) and the specific surface area Z (m 2 / g) may satisfy 1 / 30≦X2 / Z≦1 / 3. In a preferred example, in the composite particle (P) produced by the production method (M), it is possible to consider that all of the water-soluble compound (water-soluble compound containing aluminum) added to the slurry in step (ii) constitutes the layer (L). Therefore, in a preferred example, it is possible to consider that X2 is the same as the above-mentioned X1. The value of X2 / Z may be within the range exemplified for the value of X1 / Z (the range mentioned above). EXAMPLES
[0050] The present invention will be described in more detail below with reference to examples. In these examples, a number of particles were produced and evaluated. Particles A1 to A11 were produced by the above-mentioned production method (M).
[0051] (particle A1) Particles A1 were produced by the following method. First, 15 L of ion-exchanged water was added to a 20 L container. 32 g of an aqueous solution of ammonium polyacrylate (concentration: 44 mass%) and 8 kg of titanium compound particles were added to the ion-exchanged water to obtain a mixture. Barium titanate particles (BT-03 manufactured by Sakai Chemical Industry Co., Ltd., specific surface area converted particle diameter 0.25 μm) were used as the titanium compound particles.
[0052] The mixture was dispersed at 9,000 rpm for 20 minutes using a homogenizer, MARK II (manufactured by Primix Corporation), to obtain a slurry. The pH of the slurry after dispersion was 10.7.
[0053] Next, the particles in the obtained slurry were subjected to a surface treatment (the above-mentioned step (ii)) to form a layer (coating layer) of an aluminum compound on the particles. Specifically, first, while stirring the slurry using a stirrer (blade size: 130 mm, rotation speed: 110 rpm), ion-exchanged water was added to the slurry to adjust the concentration of barium titanate to 250 g / L. Then, the slurry was heated to 70° C. Next, diluted nitric acid (concentration: 5 mass%) was added to the slurry until the pH of the slurry became 8.2.
[0054] Next, 3.9 L of an aqueous solution of sodium aluminate (NaAlO2) and dilute nitric acid (concentration: 5 mass%) were added simultaneously to the slurry with a pH of 8.2. At this time, the amount of dilute nitric acid added was controlled using a pH controller so that the pH of the slurry did not deviate from the range of 8.1 to 8.4. The temperature of the slurry was maintained at 70°C. The aqueous solution of sodium aluminate was added continuously at a rate of 50 mL / min. The aqueous solution of sodium aluminate was prepared by dissolving 64.3 g of sodium aluminate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) in ion-exchanged water to a total volume of 3.9 L. 64.3 g of sodium aluminate is equivalent to 64.3 x 0.5 x 102.0 / 82.0 = 40.0 g of aluminum oxide. Therefore, the ratio X1 of the mass Wa (40 g) of sodium aluminate contained in the aqueous sodium aluminate solution in terms of aluminum oxide to the mass Wp (8000 g) of the barium titanate particles in the slurry was 0.5 mass %.
[0055] By the above process, a coating layer of an aluminum compound was formed on the composite oxide particles. Next, the slurry obtained by the above process was cooled to room temperature, and then placed in a funnel equipped with filter paper and washed with water. The washing was performed until the conductivity of the water after washing reached 80 μS / cm. Next, the cake obtained by washing was dried at 110° C. for 12 hours to obtain a dried solid. Next, the obtained solid was pulverized using an atomizer pulverizer (AIIW manufactured by Dalton Co., Ltd.) to obtain particles A1.
[0056] (particle A2) Particles A2 were produced in the same manner as the method for producing particles A1, except that the amount of ammonium polyacrylate aqueous solution, the type of barium titanate, and the amount of sodium aluminate added to the slurry were changed to prepare the mixture. Specifically, the mixture was prepared using 120 g of ammonium polyacrylate aqueous solution. For the barium titanate particles, BT-01 (particle diameter converted into specific surface area: 0.07 μm) manufactured by Sakai Chemical Industry Co., Ltd. was used. The sodium aluminate aqueous solution was added to the slurry so that the amount of sodium aluminate added to the slurry was 128.6 g. The ratio X1 of the mass Wa (80.0 g) of sodium aluminate contained in the sodium aluminate aqueous solution converted into aluminum oxide to the mass Wp (8000 g) of barium titanate particles in the slurry was 1.0 mass%.
[0057] (Particle A3) Particles A3 were produced in the same manner as the production method of particles A2, except that the amount of sodium aluminate added to the slurry was 192.9 g (X1 = 1.5 mass %).
[0058] (Particle A4) Particles A4 were produced in the same manner as the production method of particles A2, except that the amount of sodium aluminate added to the slurry was 257.2 g (X1 = 2.0 mass %).
[0059] (particle A5) Particles A5 were produced in the same manner as the production method of particles A2, except that the amount of sodium aluminate added to the slurry was 385.8 g (X1 = 3.0 mass %).
[0060] (particle A6) Particles A6 were produced in the same manner as the method for producing particles A1, except that the amount of ammonium polyacrylate aqueous solution and the type of barium titanate were changed to prepare the mixture, and the amount of sodium aluminate added to the slurry was changed. Specifically, the mixture was prepared using 495 g of ammonium polyacrylate aqueous solution. For the barium titanate particles, particles produced by hydrothermal synthesis (particle diameter converted to specific surface area: 0.02 μm) were used. The sodium aluminate aqueous solution was added to the slurry so that the amount of sodium aluminate added to the slurry was 643 g (X1 = 5.0 mass%).
[0061] (particle A7) Particles A7 were produced in the same manner as Particles A1, except that strontium titanate particles (ST-03 manufactured by Sakai Chemical Industry Co., Ltd., specific surface area converted particle diameter 0.23 μm) were used as the composite oxide particles.
[0062] (particle A8) Particles A8 were produced in the same manner as Particles A1, except that calcium titanate (CT-03 manufactured by Sakai Chemical Industry Co., Ltd., particle diameter converted into specific surface area: 0.31 μm) was used as the composite oxide particles.
[0063] (particle A9) Particles A9 were produced in the same manner as Particles A1, except that the temperature of the slurry during the surface treatment of the particles in the slurry was changed to 50°C.
[0064] (particle A10) Particles A10 were produced in the same manner as Particles A1, except that the pH of the slurry during surface treatment of the particles in the slurry was controlled to be in the range of 9.5 to 9.8 using a pH controller while adding the aqueous sodium aluminate solution to the slurry.
[0065] (Particle A11) Particles A11 were produced in the same manner as Particles A1, except that the temperature of the slurry during the surface treatment of the particles in the slurry was changed to 90°C.
[0066] (Particle CA1) Barium titanate particles that had not been subjected to a surface treatment (BT-03 manufactured by Sakai Chemical Industry Co., Ltd., particle diameter converted into specific surface area: 0.25 μm) were designated as particles CA1.
[0067] (Particle CA2) Barium titanate particles that had not been subjected to a surface treatment (BT-01, manufactured by Sakai Chemical Industry Co., Ltd., particle diameter converted into specific surface area: 0.07 μm) were designated as particles CA2.
[0068] (particle CA3) Barium titanate particles that had not been subjected to a surface treatment (particles produced by hydrothermal synthesis, particle diameter converted into specific surface area: 0.02 μm) were designated as particles CA3.
[0069] (Particle CA4) Strontium titanate that had not been subjected to a surface treatment (ST-03 manufactured by Sakai Chemical Industry Co., Ltd., particle diameter converted into specific surface area: 0.23 μm) was used as particles CA4.
[0070] (particle CA5) Calcium titanate that had not been subjected to a surface treatment (CT-03 manufactured by Sakai Chemical Industry Co., Ltd., particle diameter converted into specific surface area: 0.31 μm) was designated as particle CA5.
[0071] (particle CA6) Particles CA6 were produced in the same manner as the production method of particles A1, except that the temperature of the slurry during the surface treatment of the particles in the slurry was changed to 25°C.
[0072] (particle CA7) First, a slurry containing ammonium polyacrylate and barium titanate particles was prepared by the same method as the manufacturing method of particles A1. Next, 3.9 L of the same sodium aluminate aqueous solution used in the manufacturing of particles A1 was added to the slurry at 70°C. After the addition of the sodium aluminate aqueous solution was completed, 1.2 L of dilute nitric acid (concentration 5 mass%) was added to the slurry at an addition rate of 50 mL / min. The pH of the slurry after the addition of the sodium aluminate aqueous solution was 10.7. The pH of the slurry after the addition of the dilute nitric acid was 8.0. In this way, the surface treatment of the barium titanate particles was performed. Thereafter, the particles were treated by the same method as the manufacturing method of particles A1 to obtain particles CA7.
[0073] (particle CA8) Particles CA8 were produced in the same manner as the production method of particles A1, except that the temperature of the slurry during the surface treatment of the particles in the slurry was changed to 40°C.
[0074] (particle CA9) Particles CA9 were produced in the same manner as the production method of particles A2, except that the amount of sodium aluminate added to the slurry was 51.4 g (X1 = 0.4 mass %).
[0075] (particle CA10) Particles CA10 were produced in the same manner as the production method of particles A2, except that the amount of sodium aluminate added to the slurry was 643 g (X1 = 5.0 mass %).
[0076] (Particle CA11) Particles CA11 were produced in the same manner as the method for producing particles A1, except that the conditions for performing the surface treatment of the particles in the slurry were changed. Specifically, the temperature of the slurry during the surface treatment was changed to 50° C. In addition, the pH of the slurry during the surface treatment was controlled in the range of 5.1 to 5.4 using a pH controller.
[0077] The particles thus produced were evaluated by the following methods.
[0078] (A) Specific surface area Z and specific surface area equivalent particle diameter D SSA Measurement The specific surface area Z of particles (specifically, powder containing a large number of particles) was measured by the BET flow method using a specific surface area measuring device (Macsorb HM-1220 manufactured by Mountec Co., Ltd.). Pretreatment was performed by placing the particles under a pure nitrogen gas flow at 230°C for 30 minutes. A mixed gas of 30 volume % nitrogen and 70 volume % helium was used as the carrier gas.
[0079] Next, the specific surface area converted particle diameter D is calculated from the measured specific surface area Z using the following conversion formula. SSA was calculated. D SSA (nm) = 6 × 1000 / (S × ρ) where S is the specific surface area (m 2 / g) and ρ is the particle density (g / cm 3 ) The particle density ρ is 6.02 g / cm for BaTiO3. 3 , SrTiO3 is 4.81g / cm 3 , CaTiO3 is 3.98g / cm 3 Thus, the specific surface area converted particle diameter is the diameter of a spherical particle having the same specific surface area as the specific surface area measured for the particle of interest.
[0080] (B) Calculation of the average value Ave(La / Lp) (coverage rate) For the surface-treated particles, the above-mentioned average value Ave (La / Lp) was calculated by the following method. As described above, Lp (μm) is the average perimeter of the surface of the composite oxide particle in the cross section of the composite particle photographed with a transmission electron microscope. La (μm) is the average perimeter of the part of the surface covered with an aluminum compound layer in the cross section.
[0081] First, the particles were photographed using a transmission electron microscope (JEM-2100F manufactured by JEOL Ltd.). Specifically, 10 particles were randomly selected and photographed in a field of view magnified up to 100,000 times. From the photographed image, the perimeter Lp of the composite oxide particle was measured. In addition, the perimeter La of the portion of the perimeter Lp that was covered with a layer of an aluminum compound in the cross section was measured. Then, the value of La / Lp was calculated for each of the 10 particles. The arithmetic mean of the obtained La / Lp values was taken as the average value Ave(La / Lp).
[0082] It was confirmed by analysis that the particles that make up the composite particles are the composite oxide particles added to the slurry, and that the coating layer formed on the surface of the composite oxide particles is an aluminum compound. Specifically, this was confirmed by overlaying an element mapping image obtained by energy dispersive X-ray analysis (EDS), which can be obtained by observation with a transmission electron microscope, with a transmission electron microscope image.
[0083] (C) Evaluation of affinity to liquid 0.5g of the above particles and 9.5g of a specified liquid were placed in a test tube, and the test tube was shaken to obtain a suspension (S0) containing the particles. The suspension (S0) was left to stand at 25°C for 24 hours. As a result, the suspension separated into a suspended layer (S1) and a non-suspended layer (mainly a solvent layer). From the boundary between the two layers, the ratio (%) of the volume of the suspended layer (S1) to the volume of the suspension (S0) was calculated. The higher this ratio, the lower the sedimentation tendency of the particles and the higher their affinity with the solvent. Cyclohexanone (organic solvent) and ion-exchanged water (aqueous solvent) were used as the liquid.
[0084] (D) Measurement of the dielectric constant and dielectric tangent of particles The particles were filled into the quartz tube of a 1GHz cavity resonator (manufactured by AET Corporation), and the high-frequency dielectric constant of the particles was measured using a network analyzer P9373A (manufactured by Keysight Technologies, Inc.). The dielectric constant and dielectric tangent (tan δ) of the particles were obtained by this measurement. The measurement method conforms to JIS-C2565 "Test method for ferrite magnetic cores for microwave use."
[0085] The dielectric dissipation factor represents the proportion of electrical energy lost as heat in a dielectric when an AC electric field is applied to the dielectric. It is a particularly important characteristic for electrical and electronic components (such as capacitors) that handle high frequencies. If the dielectric dissipation factor is large, a rise in temperature can cause a decrease in insulation and malfunction of the built-in electronic circuits. For this reason, a low dielectric dissipation factor is preferable. On the other hand, a high dielectric constant is preferable.
[0086] (E) Measurement of the thickness of the aluminum compound layer (coating layer) The thickness of the layer of the aluminum compound was measured using a transmission electron microscope (JEM-2100F manufactured by JEOL). Specifically, first, 10 random particles were selected and photographed in a field of view magnified up to 100,000 times. Then, a straight line was drawn as the longest diameter of the particle. In addition, a straight line perpendicular to the longest diameter was drawn at the center of the longest diameter. The length of the line (thickness of the aluminum compound layer) at the point where these two straight lines intersect with the layer of the aluminum compound (coating layer) was measured. When the entire particle is covered with a coating layer, the two straight lines intersect with the coating layer at four points. Then, the arithmetic average of the thicknesses of the aluminum compound at the four points was taken as the average thickness of the coating layer on the particle. Note that when the straight line passes through a part where no coating layer is formed, the thickness of the coating layer at that part was calculated as zero. Then, the arithmetic average of the average thicknesses of the coating layers obtained for each of the 10 particles was taken as the average thickness of the coating layer.
[0087] Some of the manufacturing conditions and some of the evaluation results are shown in Tables 1 and 2. In the following tables, D SSA means the particle diameter converted into specific surface area. The simultaneous addition of the addition method means that the water-soluble compound is added to the slurry while maintaining the pH of the slurry in a predetermined range by adding an acid to the slurry.
[0088] [Table 1]
[0089] [Table 2]
[0090] For both cyclohexanone and water, the percentage (%) of particles exhibiting sedimentation is preferably 70% or more, more preferably 80% or more, and particularly preferably 90% or more. When the composite oxide particles are barium titanate, the dielectric constant is preferably 12 or more, more preferably 17 or more. The dielectric tangent is preferably 0.05 or less. The dielectric constant also varies depending on the type of composite oxide particles.
[0091] Particles A1 to A11 were observed and analyzed using a transmission electron microscope, etc. In particles A1 to A11, no particles formed only of aluminum compounds or parts where aluminum compounds were segregated in chunks were found, and the aluminum compounds were arranged in layers on the composite oxide particles.
[0092] As shown in the above table, the composite particles of the present invention (particles A1 to A11) produced by the production method of the present invention had high affinity for both organic solvents and aqueous solvents and had high dielectric constants. There was a tendency for the dielectric constant to decrease as the coating layer became thicker, but particles A1 to A11 had sufficiently thin coating layers and therefore showed high dielectric constants. CA10, which had a large X1 / Z value, had a low dielectric constant and a large dielectric dissipation factor. CA9, which had a small X1 / Z value, had low affinity for the solvent.
[0093] Particles A1 to A11 had high affinity for organic solvents (cyclohexanone) and aqueous solvents (water) of 70% or more. Composite particles having affinity for organic solvents and affinity for aqueous solvents of 70% or more each can be suitably used as a toner additive or a filler for resin compositions (such as resin compositions for circuit boards).
[0094] Transmission electron microscope images of particle A2, particle A3, particle CA6, and particle CA7 are shown in Figs. 1 to 4, respectively. Fig. 1 shows particle A2, Fig. 2 shows particle A3, Fig. 3 shows particle CA6, and Fig. 4 shows particle CA7. In Fig. 1, the coating layer is surrounded by a dotted line. As shown in the figure, in particles A2 and A3, the variation in the thickness of the coating layer was small, and a thin coating layer covered the surface of the composite oxide particle. On the other hand, in particles CA6 and CA7, the coating layer was aggregated in clumps, and could not be called a layer. [Industrial Applicability]
[0095] The present invention can be used in almost any method for producing composite particles.
Claims
1. The composition is of the formula ATiO 3 (wherein A represents at least one element selected from the group consisting of Ba, Sr and Ca), and a layer of an aluminum compound disposed on a surface of the composite oxide particle, comprising: (i) preparing a slurry containing the composite oxide particles by dispersing the composite oxide particles in an aqueous liquid; (ii) adding a water-soluble aluminum-containing compound and an acid to the slurry; and a step (iii) of drying the particles obtained by the step (ii), The step (ii) is carried out while maintaining the pH of the slurry in the range of 8.0 to 10.0 and the temperature of the slurry in the range of 50 to 90° C.; In the step (ii), the ratio of the mass Wa of the water-soluble compound added to the slurry in terms of aluminum oxide to the mass Wp of the composite oxide particles in the slurry is defined as X1 (mass%), and the specific surface area of the composite oxide particles is defined as Z (m 2 / g), the X1 (mass%) and the Z (m 2 / g) satisfies 1 / 30≦X1 / Z≦1 / 3.
2. The method according to claim 1, wherein in the step (ii), the water-soluble compound is added to the slurry while maintaining the pH of the slurry in the range of 8.0 to 10.0 by adding the acid to the slurry.
3. 3. The method according to claim 1, wherein the water-soluble compound is sodium aluminate and the acid is nitric acid.
4. The composition is of the formula ATiO 3 (wherein A represents at least one element selected from the group consisting of Ba, Sr and Ca), and a layer of an aluminum compound disposed on a surface of the composite oxide particle, the average value of the ratio La / Lp of the perimeter Lp (μm) of the surface of the composite oxide particle in a cross section of the composite particle photographed with a transmission electron microscope to the perimeter La (μm) of the portion of the surface covered with the layer in the cross section is 0.30 or more; The composite particle, wherein the average thickness of said layer is in the range of 1.5 nm to 4.5 nm.
Citation Information
Patent Citations
Rutile type titanium dioxide fine grain and production method thereof
JP2003327431A
Process for manufacturing dielectric ceramic raw powder
JP2003342077A
Modified perovskite type composite oxide, method for producing the same, and composite dielectric material
JP2010024094A
Modified perovskite type multiple oxide, method for producing the same and composite dielectric material
JP2010024095A
Infrared reflective material and production method thereof, and paint and resin composition containing the same
JP2010202489A